From a non‐targeted metabolomics approach to a targeted biomarkers strategy to highlight testosterone abuse in equine. Illustration of a methodological transfer between platforms and laboratories. Issue 5 (5th February 2022) - Cloteau, Chloé; Dervilly, Gaud; Kaabia, Zied; Bagilet, Florian; Delcourt, Vivian; Loup, Benoit; Guitton, Yann; Royer, Anne‐Lise; Monteau, Fabrice; Garcia, Patrice; Popot, Marie‐Agnès; Le Bizec, Bruno; et al.
Abstract: In order to overcome the challenge associated with the screening of Anabolic‐Androgenic Steroids abuses in animal competitions, a non‐targeted liquid chromatography coupled to high resolution mass spectrometry based metabolomics approach was implemented on equine urine samples to highlight potential biomarkers associated with the administration of such compounds, using testosterone esters as model steroids. A statistical model relying on four potential biomarkers intensity could be defined to predict the status of the samples. With a routine application perspective, the monitoring of the highlighted potential biomarkers was first transferred into high‐throughput liquid chromatography‐selected reaction monitoring (LC‐SRM). The model's performances and robustness of the approach were preserved and providing a first demonstration of metabolomics‐based biomarkers integration within a targeted workflow using common benchtop MS instrumentation. In addition, with a view to the widespread implementation of such biomarker‐based tools, we have transferred the method to a second laboratory with similar instrumentation. This proof of concept allows the development and application of biomarker‐based strategies to meet current doping control needs. Abstract : From non‐targeted fingerprint to targeted method to screen testosterone abuse in equine and analytical robustness evaluation between platforms and laboratories.